The business’ dilemma between the importance of a sustainable business and the responsibility to increase its profits in the Czech Republic. - Fialova, Linda; Tyll, Ladislav; Balogh, Ivan; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2023)
This thesis intends to understand the dilemma Czech organizations are facing when deciding between the necessity of a sustainable business and their obligation to increase their profit. The method of data collection used in this study was qualitative interviewing to provide a deeper understanding of participants' perceptions of what has been the organizations’ main priority and the reasons why. The Thematic analysis was used as a method for studying the qualitative data. The findings of this thesis show how a business's ability to be profitable and sustainable is equally important. And if a successful balance is established, it can benefit the entire organization. Moreover, the results indicated that while sustainability can at first require more money, it is ultimately profitable. Businesses that invest in sustainable practices can save costs, improve reputation, reduce risks, and create a more resilient and sustainable future for everyone. A firm needs to be profitable and sustainable in order to succeed. And if a successful balance is established, it can benefit the entire organization.
Vedoucí práce: Ladislav Tyll
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: management [obor dipl. práce]; diplomové práce; master's theses